Fracture behaviour of different volume fraction of alumina (AI₂O₃) reinforcement metal matrix composite / Junaidah Jai - Jai, Junaidah (2005)
Metal Matrix Composites (MMCs) are engineering materials in which a hard ceramic component is dispersed in a ductile metal matrix in order to obtain characteristics that are superior to those of the conventional monolithic metallic alloys. Due to the superior properties, MMCs are used in aerospace, automotive and other structural applications. Study on the fracture behaviour of the MMCs is necessary. Different percentage by volume (vol.%) of particulate alumina (Ah03) reinforced aluminium alloy (AI 6061) with 5 vol.%, 15 vol.% and 25 vol.% are produced by powder metallurgy method. These samples were then subjected to compressive deformation test in order to investigate the fracture behaviour of the MMCs. Microstructure analysis on the individual sample before and after testing was performed under scanning electron microscopy. It is observed that the small particles measuring below 5 urn in size exhibited strong interfacial bonding with the matrix. The particles below 20 urn to 5 urn in size have shown fracture and debonding at interface. The large particles larger than 20 urn in size have revealed severe fractures and particles pullout. Intergranular microcracks were observed propagated through and ended at the edge of the small cluster. Intergranular microcracks were only observed at the edge of the large clusters. The fracture initiation in the 5 vol.% and 15 vol.% Ah03MMCs is dominated by radial direction displacement, while in 25 vol.% Ah03 MMCs it is dominated by tangential displacement. A non-linear stress-stain profile and an increase of modulus with an increase of vol.% of Ah03 are obtained. The fracture behaviour was explained by relating the micro stuctures, stress-strain profiles , modulus and displacement directions of the undeformed and deformed MMC samples . Some understandings on the fracture behaviour of different vol.% of Ah03 reinforcement MMCs have been established.